Saliva as a matrix for human biomonitoring in occupational and environmental medicine [Biomonitoring Methods, 2015]. Issue 2 (27th April 2016) - Michalke, B.; Rossbach, B.; Göen, T.; Schäferhenrich, A.; Scherer, G.; Hartwig, A.; ,
Abstract : Purpose : Human biomonitoring ( HBM ) implies the assessment of internal exposure to hazardous substances by measuring the substances, their metabolites or reaction products, as well as effect parameters in human body fluids. Along with blood, plasma and urine, saliva is of increasing interest as an alternative matrix for HBM. Methods : This paper reviews studies that measure salivary background levels of hazardous substances, elevated levels after environmental or occupational exposure, as well as references which deal with physiological and toxicokinetic behaviour of saliva and salivary parameters, respectively. Results : The studies revealed that the determination of biomarkers in saliva is a promising approach for HBM, even if only few substances showed a satisfying correlation with exposure data or established biomonitoring matrices such as blood, plasma and urine. Saliva has been proven to be particularly suitable for substances of low molecular weight such as organic solvents, selected pesticides, cotinine, and for some specific trace elements. Besides several advantages, serious problems and limitations were identified. Above all, the complex interactions between substance properties, sampling procedure, sample preparation, measurement techniques or individual factors, and the salivary analyte level are discussed. Conclusions : A major conclusion of the review is that more scientific studies are needed in order to systematically collect data on parameters, influencing salivary analyte levels. Crucially required is a harmonisation of the sampling as well as the sample preparation techniques and procedures, which is indispensable to achieve an overall comparability and interpretability of salivary biomarker levels.